If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7n-3=11n+2
We move all terms to the left:
7n-3-(11n+2)=0
We get rid of parentheses
7n-11n-2-3=0
We add all the numbers together, and all the variables
-4n-5=0
We move all terms containing n to the left, all other terms to the right
-4n=5
n=5/-4
n=-1+1/4
| x=135+90 | | 982=58/x | | 7-3n=11+2 | | 16a-7a+2=20 | | 12p+8p-17p=-12 | | 12p+8p-17p=12 | | 2s+4s-5s-s+4s=20 | | 2y/3+1=7y/15+4 | | 2s+s+2s-4s=15 | | r+3r-3r=20 | | 2x6=32x4 | | -4j+3j-8j+15j-20j=14 | | -2(-5x-4)-6=4(3x-3)+5x | | 3-r=r-3 | | 2p-p+4p-3p=20 | | -b+6=(3b+2)-4b | | 4(-6x-2)-3(2x+8)=-62 | | 10d+d-3d=8 | | 3=24×x | | 5s-3s=18 | | 73=5/x^2 | | -2(9x-3)-7=143 | | 15h-6h-4h-5h+4h=16 | | 3x/4+1=5x/6-2 | | 3x2-2x+3=0 | | 0.7x-1.4=0.2x+1.6 | | 2(x+0.15)=1.25 | | 0.7x-1.4=0.2x+16 | | 3y2-16y+20=0 | | 6x-10=5x+6 | | 9(2x+3)=7(x+4) | | 3-x=4(2+x) |